Clinical Significance of Endogenously Labelled Thyroid Hormones in the Diagnosis of Thyroidal Autonomy - Waters, W.; Kutzim, H. (Nuklearmedizin - NuclearMedicine, 1983)
The clinical value of the determination of 123I concentration in serum 48 hrs after tracer administration (123I)48 is investigated with special regard to thyroidal autonomy. Serum radioiodine concentration, thyroid radioiodide uptake at 4 and at 48 hrs were measured in 74 healthy subjects and patients with simple goiter, in 36 patients with thyroidal autonomy (diagnosis by thyroid suppression test), and in 20 hyperthyroid patients. 83% of the patients with elevated radioiodine concentration belonged to the group of thyroidal autonomy. The product of radioiodine concentration and thyroid radioiodide uptake is a much better parameter. 95% of the patients in which this product was elevated, belonged to the autonomy group (5 % diagnostic error). Also in the control group the diagnostic error was 5 %. The combination of (123I)48 with the result of the TRH-test is very useful in excluding thyroidal autonomy, if (l23I)48 is normal and the TRHtest is positive (100% of the patients have regulated thyroid glands). 94% of the patients having elevated (123I)48 and a negative TRH-test belonged to the group of thyroidal autonomy. A very useful combination for the diagnosis of borderline hyperthyroidism is the determination of the product of (123I)48 and the uptake48 together with the pulse rate or fine tremor of the fingers (or TRH-test). The results suggest that the determination of (123I)48 is a very good parameter of thyroidal autonomy beside the thyroid suppression test. It may be used alone for the diagnosis of thyroidal autonomy if the suppression test is contraindicated. In the diagnosis of borderline hyperthyroidism its determination makes the suppression test unnecessary in many instances.